Incidence and factors associated with de novo atrial fibrillation in patients with wild-type transthyretin cardiac amyloidosis. (3rd October 2022) - Fumagalli, C; Zampieri, M; Argiro', A; Musumeci, B; Tini, G; Di Bella, G; Cipriani, A; Porcari, A; Canepa, M; Merlo, M; Sinagra, G; Rapezzi, C; et al.
Abstract: Purpose: We described the incidence and ECG factors associated with de novo atrial fibrillation (AF) in patients diagnosed with wild-type transthyretin cardiac amyloidosis (ATTRwt-CA) to drive tailored arrhythmia screening. Background: Data on the incidence rate and factors associated with de novo AF in patients with ATTRwt-CA is limited. Methods: Multicenter, retrospective, observational cohort study performed in six referral centers for CA. All consecutive patients diagnosed with ATTRwt-CA between 2004 and 2020 with >1-year follow up (FU) were enrolled in the study and were divided into three groups according to presence of AF: (1) patients with "known AF"; (2) patients in "sinus rhythm" and (3) patients developing "de novo AF" during FU. Incidence and factors associated with AF in patients with ATTRwt were the primary outcomes. Results: Overall, 266 patients were followed for a median of 469 days: 148 (56%) with known AF, 84 (31.6%) with sinus rhythm, and 34 (12.8%) with de novo AF. Age and gender were similarly distributed. At multivariable analysis, PR (Hazard Ratio [HR]: 1.008; 95% CI: 1.001–1.016), QRS (HR: 1.022; 95% CI: 1.002–1.043) and left atrial dilatation >50mm (HR: 3.429, 95% CI: 1.565–7.329) were associated with de novo AF at FU. Patients presenting with at least two risk factors (PR >200ms, QRS >120ms or LAD >50mm) had a higher risk of developing de novo AF compared to patients with no risk factors (HR 14.918; 95% CI: 3.242–31.646). Conclusions: Incidence of de novo AF in patients with ATTRwt is 20.7%/year. Longer PR and QRS duration and left atrial dilation are associated with arrhythmia onset. Funding Acknowledgement: Type of funding sources: None.